The potential of tear proteomics for diagnosis and management of orbital inflammatory disorders including Graves' ophthalmopathy. (December 2021) - Khazaei, Hadi; Khazaei, Danesh; Verma, Rohan; Ng, John; Wilmarth, Phillip A.; David, Larry L.; Rosenbaum, James T.
Abstract: Background: Orbital compartments harbor a variety of tissues that can be independently targeted in a plethora of disorders resulting in sight-threatening risks. Orbital inflammatory disorders (OID) including Graves' ophthalmopathy, sarcoidosis, IgG4 disease, granulomatosis with polyangiitis, and nonspecific orbital inflammation constitute an important cause of pain, diplopia and vision loss. Physical examination, laboratory tests, imaging, and even biopsy are not always adequate to classify orbital inflammation which is frequently deemed "nonspecific". Tear sampling and testing provide a potential "window" to the orbital disease process through a non-invasive technique that allows longitudinal sampling as the disease evolves. Using PubMed/Medline, we identified potentially relevant articles on tear proteomics published in the English language between 1988 and 2021. Of 303 citations obtained, 225 contained empirical data on tear proteins, including 33 publications on inflammatory conditions, 15 in glaucoma, 15 in thyroid eye disease, 1 in sarcoidosis (75) and 2 in uveitis (77, 78). Review articles were used to identify an additional 56 relevant articles through citation search. In this review, we provide a short introduction to the potential use of tears as a diagnostic fluid and tool to investigate the mechanism of ocular diseases. A general review of previous tear proteomics studies is also provided, with a focus on Graves' ophthalmopathy (GO), and a discussion of unmet needs in the diagnosis and treatment of orbital inflammatory disease (OID). The review concludes by pointing out current limitations of mass spectrometric analysis of tear proteins and summarizes future needs in the field. Highlights: Description of tears as a diagnostic fluid to better manage eye disease. Extensive review of tear proteomics literature. Discussion of unmet needs in treatment of orbital inflammation and promise of tear proteomics. Overview of major proteomics methods used to study tears. Discussion of limitations and future of tear biomarker research.